Assessment of population trends of common breeding birds in Lombardy, Northern Italy, 1992-2007 - BANI, LUCIANO; MASSIMINO, DARIO; ORIOLI, VALERIO; BOTTONI, LUCIANA; MASSA, RENATO IGNAZIO (Ethology Ecology & Evolution, 2009)
A knowledge of population trends is essential in order to assess the conservation status of a species and to develop practices to manage ecologically sustainable land use. However, monitoring programmes designed to assess trends are often not carried out due to their high operating costs. Therefore, in order to obtain population trend estimates without a specific monitoring programme, it is necessary to use heterogeneous historical information. The aim of this research was to assess population indices and trends between 1992 and 2007 for common bird species breeding in Lombardy (Italy), applying a previously developed method, which permits data derived from different survey projects to be utilised. Among the 51 species considered, there were seven negative and 10 positive trends, whereas the remaining species did not show a significant population change. Major declines regarded farmland species, namely the Red-backed Shrike Lanius collurio and the Sky Lark Alauda arvensis which, over a 15 year period, decreased by more than 70%. Among forest species, the Common Chiffchaff Phylloscopus collybita declined, whereas the others either increased or did not demonstrate a significant trend. The population index also highlighted recurring patterns of inter-annual changes in the populations of different species, suggesting that certain ecological processes may have an effect on the whole community. The general decline of farmland species, which is known to occur in many other European regions, suggests the need for specific monitoring schemes for birds and their habitats, in order to understand the effects of changes in agricultural practices and to be able to plan effective measures for bird conservation in productive areas.